Juridical Implications Of Family Card Issuance For Siri Marriage Couples On Child Status - Abdul Kodir; Hanif Nur Widhiyanti; Rachmi Sulistyarini (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Marriage is not legally valid or not listed as an issue that is hotly discussed in various perspectives. Registration of marriage is basically necessary as a protection of the state to the parties to the marriage, and also to avoid the tendency of inconsistency in the application of religious teachings and beliefs in a perfect or intact marriage that took place according to religion and belief. This study is a type of normative juridical research. This is because normative juridical research is the type of research that is most relevant to the conflict of norms that occurs and can find detailed and detailed answers to the formulation of the problem to be studied. Based on the Marriage Act No. 1 of 1974 article 1 that marriage is the inner and outer bond between a man and a woman as husband and wife whose purpose is to form a prosperous and eternal family based on the Supreme Godhead. Understanding the inner inner Bond in this marriage is a bond or legal relationship between one man and one woman whose purpose is to live together as husband and wife status. According to the Quran a Muslim is one who has absolutely surrendered to Allah and his commands and believes in pure Tawhid (the oneness of God) that isn't tainted with any shirk and this is why the Almighty has introduced prophet Abraham as a true worshipper. In The Marriage Act No.1 of 1974 Article 2 Paragraph (1) explained that marriage is valid if it is done according to religion and beliefs, with the added sound in Paragraph (2) that each marriage is recorded according to applicable laws and regulations. If the marriage is valid, then the child born from the marriage will obtain legal status as a legitimate child as stipulated by Article 42 of the marriage law. It can be concluded that if the marriage is invalid, then the child born from the marriage does not occupy the position of a legitimate child.